Protein Engineering of Multi-Modular Transcription Factor Alcohol Dehydrogenase Repressor 1 (Adr1p), a Tool for Dissecting In Vitro Transcription Activation - Memmo Buttinelli; Gianna Panetta; Ambra Bucci; Daniele Frascaria; Veronica Morea; Adriana Erica Miele (Biomolecules, 2019)
Studying transcription machinery assembly in vitro is challenging because of long intrinsically disordered regions present within the multi-modular transcription factors. One example is alcohol dehydrogenase repressor 1 (Adr1p) from fermenting yeast, responsible for the metabolic switch from glucose to ethanol. The role of each individual transcription activation domain (TAD) has been previously studied, but their interplay and their roles in enhancing the stability of the protein is not known. In this work, we designed five unique miniAdr1 constructs containing either TADs I-II-III or TAD I and III, connected by linkers of different sizes and compositions. We demonstrated that miniAdr1-BL, containing only PAR-TAD I+III with a basic linker (BL), binds the cognate DNA sequence, located in the promoter of the ADH2 (alcohol dehydrogenase 2) gene, and is necessary to stabilize the heterologous expression. In fact, we found that the sequence of the linker between TAD I and III affected the solubility of free miniAdr1 proteins, as well as the stability of their complexes with DNA. miniAdr1-BL is the stable unit able to recognize ADH2 in vitro, and hence it is a promising tool for future studies on nucleosomal DNA binding and transcription machinery assembly in vitro.